Synergistic strategies in photodynamic combination therapy for cancer: mechanisms, nanotechnology, and clinical translation - Kan, Daohong; Ding, Rong; Yang, Huchuan; Jia, Yuming; Lei, Kaijian; Wang, Zhongming; Zhang, Wei; Yang, Chaokun; Liu, Zongjunlin; Xie, Fang (Frontiers in Oncology, 2025)
Photodynamic therapy (PDT), a non-invasive and highly selective method for cancer treatment, has gained increasing attention due to its unique ability to activate a photosensitizer with near-infrared laser irradiation, generating reactive oxygen species (ROS) and inducing cytotoxic effects on tumors. However, PDT faces challenges such as the shallow penetration depth of the laser impacting treatment efficacy and the variability in ROS yield depending on various factors. Recent advancements in nanotechnology have paved the way for solutions, showing promising results in addressing these limitations. Therefore, there is rising interest in utilizing PDT in combination with other therapeutic modalities to enhance its anti-tumor efficacy. This review aims to compile relevant basic experiments and clinical studies on the principles, mechanisms, and various combination therapies of PDT, including with photothermal therapy, radiotherapy, chemotherapy, targeted therapy, and immunotherapy. The findings from these studies consistently confirm that photodynamic combination therapy achieves a higher therapeutic index with lower side effects compared to the use of these modalities individually. The demonstrated synergistic effects and enhanced therapeutic outcomes in various studies underscore the need for additional research and development in this direction.